Effect of intellectual impairment on basketball game-related statistics - Pinilla, J.; Perez-Tejero, J.; Van Biesen, D.; Vanlandewijck, Y. (Collegium Antropologicum, 2016)
The purpose of this study was to analyze the influence of intellectual impairment (II) on game-related statistics which best contribute to success in basketball. Official game-related statistics were gathered from 6 male teams (n=63 players) during the 13 games played in the World II-Basketball Championships (Ankara 2013). Variables were normalized to 100 ball possessions and descriptive statistics were calculated. To identify which variables contributed best to success, a discriminant analysis was performed. The obtained structural coefficients (SC) in the discriminant function pointed out 2-pt successful ¦SC=-0.65¦, assists ¦SC=-0.61¦, steals ¦SC=-0.41¦ and offensive rebounds ¦SC=-0.32¦ as variables which best contributed to success. Results were compared with previous studies in able-bodied (AB) basketball. Assists and 2-point successful were discriminant variables of success in II and AB-competitions; however, defensive rebounds were discriminant in many AB but not in any II-competition. In addition, steals and offensive rebounds were only discriminant variables in II-basketball. Relevancy of assists reflected the importance of teamwork in both AB and II-basketball; however, the lower shooting efficiency presented in II-players seem to indicate limitations on decision making capacity and tactical offense to reach the best option to shoot. Consequently, second opportunities to score (offensive rebounds) and scoring under low defensive pressure (fast-break after a steal); seem to take relevance to increase 2-point successful in II-players. These findings confirm the negative influence of II on basketball game-related statistics and this is a first necessary step to develop basketball-specific eligibility systems required to include II-basketball in the Paralympic program.